Muscle Activation Pattern During Isometric Ab Wheel Rollout Exercise in Different Shoulder Angle-Positions - Marchetti,Paulo Henrique (2015)
OBJECTIVE: To investigate muscle activation of the shoulder extensors and trunk stabilizers by surface electromyography (sEMG) activity during the isometric Ab Wheel Rollout exercise in different shoulder joint positions. METHOD: We recruited 8 young, healthy, resistance trained men (age: 25 ± 3 years, height: 178 ± 5 cm, and total body mass: 81 ± 2 kg). All subjects performed two sets of 10 sec. maximal isometric contractions of the Ab Wheel Rollout exercise keeping the knees fixed on the floor and the arms taut. To perform the exercise, all subjects were randomly assessed in the following three positions related to the angle between the arms and trunk, in random order: arms aligned vertically with the Ab Wheel Rollout exercise (neutral); 90º and 150º. A rest period of 5 minutes was provided between tests. The sEMG signals were recorded in the following muscles: Latissimus Dorsi; Pectoralis Major; Erector Spinae; Rectus Abdominis. RESULTS: There were significant increases in Rectus Abdominis muscle activity between: neutral vs. 90º, neutral vs. 150º and 90º vs. 150º. There was a significant increase in Pectoralis Major muscle activity between neutral x 150º. CONCLUSION: The present findings indicate that (a) Ab Wheel Rollout exercise emphasizes the muscle action of the Pectoralis Major and Rectus Abdominis more than the Latissimus Dorsi and Erector Spinae; (b) the level of muscle activation depends on the external force created by the body mass and lever arm from the center of mass.